About stability of levitating states of superconducting myxini of plasma traps-Galateas - Bishaev, A.M.; Bush, A.A.; Gavrikov, M.B.; Denis’uk, A.I.; D’yakonitsa, O.Y.; Kamentsev, K.Y.; Kozintseva, M.V.; Kolesnikova, T.G.; Savelyev, V.V.; Smirnov, P.G.; Shapovalov, M.M.; Voronchenko, S.A. (Вопросы атомной науки и техники, 2015)
To develop a plasma trap with levitating superconducting magnetic coils it is necessary to carry out the search of their stable levitating states. With this purpose, based upon the superconductor property to conserve the trapped magnetic flux, in the uniform gravitational field the analytical dependence of the potential energy of one or two superconducting rings, having trapped the given magnetic fluxes, in the field of the fixed ring with the constant current from the coordinates of the free rings and the deflection angle of their axes from the common axis of the magnetic system has been obtained in the thin ring approximation. Under magnetic fluxes of the same polarity in coils the existence of the found from the calculations equilibrium levitating states for the manufactured HTSC rings stable relative to the vertical shifts of levitating rings and to the deflection angle of their axes from the vertical has been confirmed experimentally.